Structural diagenesis and dolomitization of Cenozoic post-rift carbonates in the Red Sea rift basin: A multiproxy approach - Herlambang, Adhipa; Koeshidayatullah, Ardiansyah I.; Amao, Abduljamiu O.; Bello, Abdulwahab M.; Al-Ghamdi, Faisal; Malik, Muhammad H.; Al-Ramadan, Khalid A. H. (Frontiers in Earth Science, 2022)
Middle Miocene post-rift sediments are considered prolific subsurface reservoirs, representing one of the thickest sequences in the Red Sea rift basin. In the Umm Luj Basin of the eastern Red Sea, post-rift sediments are well exposed and represented by a carbonate-dominated system of the Raghama Formation. This formation was intensely fractured, following the rifting trend of the Red Sea. Such fractures and their associated diagenetic products could provide a significant archive of past tectonic fluid evolution. However, little is known about the origin and timing of the different fluid flows and diagenetic processes in the area. This study aims to resolve this issue by integrating fracture and multiproxy geochemical analyses of calcite precipitated in veins, fault breccia, and dolomitized host rock. The δ18O and δ13C isotopic compositions of calcite veins show tight clustering, varying between −10.6 and −9.5‰ and between −7.9 and −7.2‰, respectively. Meanwhile, the precipitated calcite along the fault breccia exhibited a closer to host rock isotopic composition (δ18O = −6.8‰; δ13C = −4.8‰). The δ18OVPDB of the dolomitized host rock shows a heavier average value, closer to the expected range of Miocene seawater. X-ray diffraction analysis shows that the veins have a high magnesium calcite content (up to 79.5%). In contrast, all the host rock samples, except samples 1-1BH, have dolomite contents of up to 94.3%, as well as breccia fragments. Thus, we argue that the structural diagenesis history of the study area comprises two distinct fluid members and tectonic events. The first member is the deposition of heavier isotopic composition related to dolomitization at slightly higher temperatures of up to 42.2°C. The second fluid flow member corresponded to a depleted isotopic calcite member with a temperature of 33°C. Compared with the Midyan Peninsula, the study area shares the same regional tectonic events, but the local tectonic and depositional settings could act as the determining factors of the dolomitization mechanism and meteoric alteration in each location. Hence, our results provide a new understanding of paleo-fluid circulation related to the evolution of tectonic events and highlights the value of integrating fracture and multiproxy geochemical analysis for structural diagenetic studies.